CARNITINE SUPPLEMENTATION EFFECTS on NONENZYMATIC ANTIOXIDANTS IN YOUNG RATS SUBMITTED TO EXHAUSTIVE EXERCISE STRESS - Bucioli, Servio A.; De Abreu, Luiz C.; Valenti, Vitor E. [UNESP]; Vannucchi, Helio (Lippincott Williams & Wilkins, 2012)
Bucioli, SA, de Abreu, LC, Valenti, VE, and Vannucchi, H. Carnitine supplementation effects on nonenzymatic antioxidants in young rats submitted to exhaustive exercise stress. J Strength Cond Res 26(6): 1695-1700, 2012-Previous studies have demonstrated that exercise stress increases oxidative stress in rats. However, antioxidant supplement therapy effects on reactive oxygen substances are conflicting. We evaluated the effects of carnitine on renal nonenzymatic antioxidants in young rats submitted to exhaustive exercise stress. Wistar rats were divided into 3 groups: (a) control group (not submitted to exercise stress), (b) exercise stress group, and (c) exercise stress and carnitine group. The rats from group 3 were treated with gavage administration of 1 ml of carnitine (5 mg.kg(-1)) for 7 consecutive days. The animals from groups 2 and 3 were submitted to a bout of swimming exhaustive exercise stress. Kidney samples were analyzed for reactive substances to thiobarbituric acid by malondialdehyde (MDA), reduced glutathione (GSH), and vitamin-E levels. Carnitine treatment attenuated MDA increase caused by exercise stress (1:0.16 +/- 0.02 vs. 2:0.34 +/- 0.07 vs. 3:0.1 +/- 0.01 mmmol per milligram of protein; p < 0.0001). It also increased the renal levels of GSH (1:23 +/- 4 vs. 2:23 +/- 2 vs. 3:58 +/- 9 mu mol per gram of protein; p, 0.0001); however, it did not change renal vitamin E (1:24 +/- 5 vs. 2:27 +/- 1 vs. 3:28 +/- 5 mu M per gram of tissue; p < 0.001). In conclusion, carnitine improved oxidative stress and partially improved the nonenzymatic antioxidant activity in young rats submitted to exhaustive exercise stress.
Keywords: free radicals; carnitine; stress; exercise